Pengaruh Penggunaan Strategi Pemasaran Gerilya Dan Online Customer Review Terhadap Peningkatan Minat Beli Konsumen ( Studi Kasus UMKM Fashion Muslim Wnj.Id) - Pitaloka, Sonia; Lukitasari, Lenni (CV. ITTC INDONESIA, 2024)
This study aims to determine the impact of guerrilla marketing strategies on WNJ ID, how influential guerrilla marketing strategies and online customer reviews are on increasing consumer buying interest. The research method used in this study used a qualitative approach with a descriptive method, and the data collected came from interviews and direct observation. The results showed that the synergy between guerrilla marketing strategies and online customer reviews can strengthen the influence on increasing consumer buying interest. When businesses implement guerrilla marketing strategies that create memorable experiences, and are supported by positive online customer reviews, consumers tend to be more confident and interested in buying products or using these services. WNJ ID has implemented guerrilla marketing and online customer reviews to increase consumer buying interest. From the results of the interview, the influence of guerrilla marketing strategies and online customer reviews has a significant influence on increasing consumer buying interest. The use of creative and unique guerrilla marketing strategies can generate consumer buying interest by creating memorable experiences. Meanwhile, positive online customer reviews can build consumer trust and confidence in the product.